"From Palestine to Mexico, all the walls have got to go": rhetorical bordering as transnational settler colonial project. Issue 1 (2nd January 2021) - Masri, Hana
ABSTRACT: This essay analyzes the conditions that make comparisons between the US-Mexico borderlands and Palestine-Israel rhetorically resonant in the discourse of politicians and political organizers. Such comparisons offer insight on the communication of borders and how scholars should analyze it. I suggest that turning to the Palestinian context evidences a stringent need for scholars of rhetorical bordering to attend to situations outside of the US because borders—and coalitional social movements against them—cannot be understood in isolation. The settler colonial conditions that connect border contexts across distinct geographies speak to how rhetoric sparks shared border violences transnationally, from Palestine to Mexico.